Study of Tuberculosis (TB) Management Documentation with Directly Observed Treatment Short Strategy Course (DOTS) in Puskesmas, Hospital, and Lung Disease Treatment Unit (UP3) - Slamet, R Sunarko; Josef, Hari Kusnanto; Claramita, Mora (Review of Primary Care Practice and Education, 2024)
Background: WHO suggests that pulmonary TB is a global emergency for humans since 1993. Where the burden of TB disease in the community is still very high, it is estimated that there are still about 9.5 million new TB cases, and about 0.5 million deaths caused by TB worldwide. WHO Global Tuberculosis Report states that TB is still a major health issue even though TB is a preventable and treatable disease. WHO Global Tuberculosis Report argues that TB has existed from the first millennium to the millennium and is still a global health problem. Objectives: Monitoring and evaluation is one of the most vital management functions to assess the success rate of TB program implementation. The presence of regular and ongoing monitoring functions to detect problems early in the implementation of planned activities so that they can be fixed as soon as possible. This evaluation also assesses the extent to which the predetermined objectives and outcomes have been achieved at the end of the period. In conducting the assessment of success, indicators, and standards. Method: The method although initially rarely considered in qualitative research methodologies, is today an important and integral part of the qualitative research methodology. This is due to the growing awareness and new understanding in the researchers, that a lot of data is stored in the form of documents and artifacts. So that the excavation of data sources through document studies becomes complementary to the qualitative research process. Even Guba as quoted by Bungin states that the use and use of existing documents determines the credibility level of a qualitative research result. Result: The results showed that all health facilities in Puskesmas, hospitals, and UP3 had followed TB management with DOTS strategy. In general, implementing the five DOTS pillars at puskesmas was better than in hospitals and UP3, but supporting documents on DOTS pillar implementation in hospitals and UP3 were more complete.  Conclusion: The achievement of the DOTS program at the health service facility conducted by the research shows that the puskesmas is better than the hospital and UP3.